The hegemon's tool kit US leadership and the politics of the nuclear nonproliferation regime - Gibbons, Rebecca Davis (Cornell studies in security affairs., 2022)
"Rebecca Davis Gibbons argues that the nuclear nonproliferation regime is a fundamental part of the US-led global ordering project, that Washington, DC, has long persuaded other states to join this regime such that a decline in US relative power could result in nuclear proliferation"--